2019
DOI: 10.3390/ani9090663
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Milk Coagulation Properties and Individual Cheese Yield in Sheep Using Partial Least Squares Regression

Abstract: Simple SummaryConsidered that all sheep milk in Italy is destined for cheese processing, traits describing rennet coagulation aptitude should be among the most important selection goals for dairy breeds. To reduce the costs and logistics related to the large-scale recording of these traits, mid-infrared (MIR) spectroscopy could be conveniently used to generate reliable predictions without any additional cost. The aims of this research were to predict the milk coagulation properties (MCP) and individual cheese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
1
13
1
Order By: Relevance
“…Individual cheese yield based on micro-cheese manufacturing (ILCY) was first described by Othmane et al (2002a) as a useful predictor of actual cheese yield. Individual cheese yield can also be predicted by spectroscopy, as Othmane (2000) and Cellesi et al (2019) showed. However, the laboratory simulation process of individual cheese manufacturing followed in this study is not completely comparable to that of the dairy industry.…”
Section: Phenotype Basic Statistics and Genotype Quality Filteringmentioning
confidence: 97%
See 1 more Smart Citation
“…Individual cheese yield based on micro-cheese manufacturing (ILCY) was first described by Othmane et al (2002a) as a useful predictor of actual cheese yield. Individual cheese yield can also be predicted by spectroscopy, as Othmane (2000) and Cellesi et al (2019) showed. However, the laboratory simulation process of individual cheese manufacturing followed in this study is not completely comparable to that of the dairy industry.…”
Section: Phenotype Basic Statistics and Genotype Quality Filteringmentioning
confidence: 97%
“…As other authors have suggested, micro-cheese factoring can determine an overestimation of the actual cheese yield due to the limited amount of milk used (Puledda et al, 2017;Othmane et al, 2002b;Jaramillo et al, 2008). In any case, ILCY is the most commonly used parameter for the calculation of the individual laboratory cheese yield, and many different studies have used it as a good proxy trait to assess the cheese-making ability of dairy species (Othmane et al, 2002b,c;Cellesi et al, 2019). Because genetic selection relies on individual phenotype values, the individual proxy phenotypes here analyzed for MCP and cheese yield traits may be of great value for those breeding programs of dairy species that define the improvement of milk technological properties selection objectives.…”
Section: Phenotype Basic Statistics and Genotype Quality Filteringmentioning
confidence: 99%
“…An interesting tool to investigate reasons for occurrence of NC milks is mid-infrared (MIR) analysis; MIR spectroscopy is routinely used for predicting milk composition traits in dairy recording programs. Milk MIR spectra have also been exploited to predict other phenotypes for which the standard analysis procedures are expensive and time consuming; for example, milk fatty acid (Soyeurt et al, 2011) and mineral (Visentin et al, 2018) composition, cheese-making properties (De Marchi et al, 2009;Cellesi et al, 2019), body energy status (McParland et al, 2011), pregnancy status (Brand et al, 2021), and feed composition and intake (Klaffenböck et al, 2017;Wallén et al, 2018). The use of milk spectra to predict the milk fatty acid profile allowed the use of these phenotypes for genomic predictions in Sarda dairy sheep (Cesarani et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Third, we selected ILCY, which provides information about cheese yield performance. The ILCY trait has previously been detailed as a useful predictor of the actual cheese yield (Othmane et al, 2002b) and declared by different studies as a good proxy trait for assessing the cheese-making ability of dairy species (Othmane et al, 2002a;Cellesi et al, 2019). Both the logK 20 and ILCY traits have been previously suggested as potential candidate traits to be considered for future inclusion in the selection index of the Assaf sheep breed to improve the cheese-making ability of this breed, and they were used together with PP due to the high reported genetic correlation of PP with ILCY (Sánchez-Mayor et al, 2019).…”
Section: Phenotype Descriptive Statistics and Genotype Quality Filteringmentioning
confidence: 99%